Case Report: Clinical and Procedural Implications of Ommaya Reservoir Implantation in Cystic Brain Metastases Followed by Radiosurgery Treatment - Lv, Junhui; Wu, Zhuoxuan; Wang, Kun; Wang, Yirong; Yang, ShuXu; Han, Weidong (Frontiers in Surgery, 2022)
Background: Therapy for large or deep cystic brain metastases is a troublesome problem in clinical departments. Stereotactic cyst aspiration combined with gamma knife radiosurgery can be an effective treatment for cystic brain metastases. However, there is still a possibility that reaccumulation of cystic fluid may lead to poor efficacy or even reoperation. Case presentation: We present a case of a 67-year-old man who was diagnosed with lung cancer brain metastasis. The intracranial lesion seen on imaging appeared to be cystic and located deep in the brain with associated limb dysfunction. The patient did not respond well to chemotherapy and underwent cyst aspiration with Ommaya reservoir implantation under neuronavigation. Repeated cystic fluid reaccumulation and exacerbation of symptoms occurred during treatment. We performed repeated aspiration via the Ommaya reservoir to control the symptoms and combined it with radiotherapy. During the follow-up period of 14 months, the intracranial tumour was effectively and satisfactorily controlled. Conclusions: We highlight that Ommaya reservoir implantation during stereotactic cyst aspiration is necessary to prevent fluid reaccumulation, avoiding the need for a second surgical procedure.